The problem requires the solution of a differential equation. The first step in this case is let "dy" alone as follows:
![dy=(10x-12x^3)dx](https://img.qammunity.org/2023/formulas/mathematics/high-school/ivjpu9j6jubte3c13pe1svftlueuw4wkgw.png)
Now we have to integrate each part of the equality.
![\int dy=\int(10x-12x^3)dx](https://img.qammunity.org/2023/formulas/mathematics/high-school/ywbzhdyaq1vyjqjkod3whw7m5gn2pynhat.png)
The left side is the integral of "1":
![\int dy=y+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/96bnxceg6r44msbes6caomumu94fpmg7zy.png)
Where "c" is a unknown constant. Now the right side as follows:
![\int(10x-12x^3)dx=5x^2-3x^5](https://img.qammunity.org/2023/formulas/mathematics/high-school/u2uznzq27wfuzbnvhvp5dc8vibqrb014lp.png)
Where we did not add another constant becase we already did it on the left side of the equation. Now:
![\begin{gathered} y+c=5x^2-3x^5 \\ y=5x^2-3x^5-c \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7cbdz76kmr0wkkvn2hzp5zmpdznr7hm4gi.png)
Finally, we consider the initial condition y(3)=2 to find the value of "c" as follow:
![\begin{gathered} y(3)=5(3)^2-3(3)^5-c=2 \\ 5(3)^2-3(3)^5-2=c \\ c=-686 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jcxfe0a6m9r49yb8anth8crz5sjdot2sxl.png)
Hence, the particular solution is:
![y=5x^2-3x^5+686](https://img.qammunity.org/2023/formulas/mathematics/high-school/drku67d1oov9cr03936nmy0yge7pggdtz5.png)